The complete guide to teaching a course : practical strategies for teachers, lecturers and trainers - Forsyth, Ian.; Jolliffe, Alan.; Stevens, David (London : Kogan Page, 1999)
Designed to guide teachers and trainers in the preparation of course materials, this work offers suggestions on selection criteria. It also covers such issues as innovation, the open learner, the different types of materials available, and how to prepare material for other teachers
Includes bibliographical references and indexes.
Keywords: Instructional systems -- Design; Curriculum